MQTT Protocol-Based ESP-32 Smarthome with Multi-sensor Recognition - Febriansyah Dwicahya Makatita; Nurul Fahmi Arief Hakim (Universitas Sebelas Maret (UNS), 2024)
Rapid technological advancements are accompanied by a progressive increase in sophistication. Nonetheless, an issue that must not be overlooked in light of this progress pertains to the energy sources employed. One possible resolution to this issue involves the implementation of an automation system within the domestic setting. Therefore, the objective of this study was to develop an automation system for use in a smarthome or residential setting. In addition to this, the objective of this study is to assess the efficacy of the smarthome application and streamline the system in comparison to prior investigations. Following a literature assessment, the research methodology consists of system design, system development, and system testing. Based on the conducted research, it was determined that the temperature sensor employed exhibited a commendable accuracy rate of 98.12%. Positive outcomes were also obtained through the implementation of the MQTT protocol in this study; the MQTT Dashboard application exhibited an average delay of 0.725 seconds, while the node-red application demonstrated a delay of 0.67 seconds. It can be concluded from these results that the designed and implemented system functions as intended. Additionally, these results indicate that the implementation of a smarthome system can streamline the management of routinely utilized electronic devices. In addition to this, the implementation of the sensors yields favorable outcomes, thereby establishing their dependability for the regulation of automated systems. With any luck, this study will offer a comprehensive understanding of the potential of smarthomes as a sustainable alternative that will inspire greater attention to energy conservation in the home environment.